Motives of patients crossing borders to pursue assisted reproduction - why the Czech Republic is a frequent choice for egg donation treatment - Dostálová, Anna; Güell, Francisco (Ceska gynekologie, 2022)
Cross-border reproductive care is undoubtedly a current phenomenon. The number of people interested in receiving reproductive care abroad is increasing every year. This new context needs a political solution that would respond to the definition of standard care within the circumstances of providing healthcare to the citizens of another country. Patients that undergo reproductive treatment abroad very often face complications such as language problems, insufficient information, separation from family members, cultural differences and customs, potential unrealistic expectations, and also restrictions by law. This work is descriptive in nature and aims to illustrate the variables that come into play when choosing the Czech Republic over other destinations as a country to receive infertility treatment. We analyze the phenomenon by selecting documents used as sources of data. In our research, we focused on infertility treatment and justified the reasons why foreign citizens choose the Czech Republic over other destinations for infertility treatment. The variables that lead to the selection of cross-border infertility treatment in the Czech Republic include no waiting time, anonymous donations, international departments in various languages, and affordable prices compared to other destinations.
Keywords: fertility clinics; Humans; ovum donors; Czech Republic; infertility; motivace; Reproductive Techniques, Assisted; in vitro techniques; Česká republika; infertilita; asistovaná reprodukce; medical tourism; Reproduction; rozmnožování; Infertility; zdravotní turistika; Medical Tourism; lidé; Motivation